2007
DOI: 10.1521/jscp.2007.26.3.362
|View full text |Cite
|
Sign up to set email alerts
|

Written Emotional Disclosure: Testing Whether Social Disclosure Matters

Abstract: Studies suggest that written emotional disclosure can improve health. Unknown, however, is whether the presence or absence of an audience for one's disclosure matters, and whether time management control writing has any effects. Undergraduates (N = 165) with unresolved stress were randomized to 1 of 3 groups that wrote for 4 sessions: shared written disclosure (submitted to researchers), private written disclosure (not submitted), or time management control writing; or to a fourth group (no-writing control). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 42 publications
2
35
1
2
Order By: Relevance
“…Our null findings for self-reported physical health were somewhat surprising given that numerous studies have reported self-reported physical health benefits associated with expressive writing (e.g., Greenberg et al, 1996; Norman, Lumley, Dooley, & Diamond, 2004; Pennebaker, Colder, & Sharp, 1990; Pennebaker & Francis, 1996; Radcliffe, Lumley, Kendall, Stevenson, & Beltran, 2007; Sheese et al, 2004), and Frattaroli's (2006) meta-analysis indicated a significant effect size for self-reported physical health ( r = .056). Several possible factors might account for the null findings observed for physical health.…”
Section: Discussioncontrasting
confidence: 72%
“…Our null findings for self-reported physical health were somewhat surprising given that numerous studies have reported self-reported physical health benefits associated with expressive writing (e.g., Greenberg et al, 1996; Norman, Lumley, Dooley, & Diamond, 2004; Pennebaker, Colder, & Sharp, 1990; Pennebaker & Francis, 1996; Radcliffe, Lumley, Kendall, Stevenson, & Beltran, 2007; Sheese et al, 2004), and Frattaroli's (2006) meta-analysis indicated a significant effect size for self-reported physical health ( r = .056). Several possible factors might account for the null findings observed for physical health.…”
Section: Discussioncontrasting
confidence: 72%
“…Negative emotional sharing may reduce the intensity of fear (Langens, 2005), traumatic stress (Greenberg & Stone, 1992), and depression (Radcliffe, Lumley, Kendall, Stevenson, & Beltran, 2010). It can also relieve the stress of suppressing negative feelings and allow reappraisal of the negative experience (Pennebaker, 1997;Pennebaker & Beall, 1986;Rimé, 2009).…”
Section: Emotional Disclosure On Facebookmentioning
confidence: 99%
“…Reis and Shaver (1988), in their interpersonal process model, proposed that reciprocal selfdisclosure in the early stages of relationships is critical to establishing the mutual trustworthiness necessary to progress to greater intimacy. Mutual self-disclosure leads to perceived similarity and liking, which in turn facilitate relationship formation and satisfaction (e.g., Collins & Miller, 1994;Laurenceau, Barrett, Feldman, & Pietromonaco, 1998;Radcliff, Lumley, Kendall, Stevenson, & Beltran, 2007;Reis, Sheldon, Gable, Roscoe, & Ryan, 2000;Vittengl & Holt, 2000).…”
Section: Circumplex and Relational Modelsmentioning
confidence: 99%